Omalizumab in the Therapy of Pediatric Asthma - Poddighe, Dimitri; Brambilla, Ilaria; Licari, Amelia; Marseglia, Gian L. (Recent Patents on Inflammation & Allergy Drug Discovery, 2018)
Background: Eosinophilic asthma is driven by Th2 immune response and is usually characterized by the increase of total serum IgE levels and/or specific IgE that express single or multiple allergen sensitization. In such an immuno-pathological background, the anti-IgE therapy, namely omalizumab, found its main clinical utility and recommendation to treat severe asthma. Objective: In this mini-review, we summarized the most relevant immuno-pathological and clinical evidences supporting the use of omalizumab in the therapy of pediatric asthma. Furthermore, we provided the main practical points for its use in the therapeutic management of asthmatic children. Method: Through the binding of serum free IgE, omalizumab impairs not only the effector phase of IgE-mediated asthma, but also affects the IgE biology and the related immune response, globally. Here, the history of omalizaumab has been shortly reviewed from its preclinical development to its clinical validation in pediatric asthma. Thus, recent patents regarding anti-IgE therapy have been discussed. Conclusion: Omalizumab significantly improved the clinical management of severe and uncontrolled pediatric asthma; however, pre-treament IgE levels limited the use of omalizumab in some patients and the cost of the therapy is still relevant. Moreover, the optimal duration of the treatment with omalizumab in children has to be determined. Finally, the recent generation of a mutant IgE-Fc fragment being resistant to omalizumab binding might open further therapeutic applications, in addition to second generation anti-IgE antibodies.
Keywords: pediatric asthma